STUDENTS’ MATHEMATICS PROBLEM-SOLVING ABILITY WITH KINESTHETIC LEARNING STYLE AT VOCATIONAL SCHOOL - Firdaus, Andi Mulawakkan; Herwandi, Herwandi (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
According to the interview results, students of SMK Muhammadiyah 2 Bontoala Makassar have good mathematical problem-solving skills. However, some students still find it difficult to solve math issues in the form of non-routine questions. According to other research, learning styles, notably kinesthetic learning styles, have a considerable impact on students' ability to solve mathematical problems. This study aims to describe the profile of students' mathematical problem-solving abilities based on Polya's theory (understand, strategy, solve and look back) in terms of kinesthetic learning styles. This type of research is descriptive qualitative research, and the data collection techniques in this study used three ways, namely filling out questionnaires, giving tests, and interviews. From the data collection techniques, the results obtained that two (2) students with kinesthetic learning styles have high problem-solving scores with an average of 77.5 and only fulfill three stages of problem-solving based on Polya's theory. Therefore, the teacher must pay attention to the tendency of kinesthetic learning styles in order to be able to improve students' mathematical problem-solving abilities. Abstrak: Berdasarkan pada hasil wawancara yang diperoleh, menyatakan bahwa siswa SMK Muhammadiyah 2 Bontoala Makassar yang mempunyai kemampuan memecahkan masalah matematika yang baik, ternyata masih terdapat beberapa siswa yang sulit dalam menyelesaikan soal matematika berbentuk masalah non rutin. Data lain menyatakan bahwa kemampuan pemecahan masalah matematika siswa dipengaruhi oleh gaya belajar secara signifikan termasuk gaya belajar kinestetik. Tujuan penelitian ini adalah untuk mendeskripsikan profil kemampuan pemecahan masalah matematika siswa berdasarkan teori menurut Polya (understand, strategy, solve dan look back) ditinjau dari gaya belajar kinestetik. Jenis penelitian ini adalah penelitian kualitatif deskriptif, teknik pengumpukan data pada penelitian ini menggunakan tiga cara yaitu pengisian kuesioner, pemberian tes dan wawancara. Dari teknik pengumpulan data tersebut, maka diperoleh hasil penelitian bahwa 2 orang siswa dengan gaya belajar kinestetik mempunyai nilai pemecahan masalah yang tinggi dengan rata-rata 77,5 dan hanya memenuhi tiga tahap pemecahan masalah berdasarkan teori Polya. Oleh karena itu guru harus memperhatikan kecenderungan gaya belajar kinestetik agar mampu meningkatkan kemampuan pemecahan masalah matematika siswa.